1999
DOI: 10.1177/000348949910800605
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Antiallergic Drug on Otitis Media with Effusion in Association with Allergic Rhinitis; An Experimental Study

Abstract: The effect of an antiallergic drug on the evacuation of middle ear effusion (MEE) from the tubotympanum was investigated by means of an animal model with both otitis media with effusion (OME) and allergic rhinitis. Azelastine hydrochloride (AZ), an oral antiallergic drug, was administered and the presence of MEE was investigated. Serous MEE was seen in 12 of the 13 untreated control animals on the 11th day after the experimental OME was induced, whereas MEE was detected in 9 of the 13 animals administered 1 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Albumin concentration in the middle ear exudates was also reduced with the addition of OLO. Our work supports the results of Suzuki et al 23 that demonstrated that oral AZE promoted the evacuation of middle ear effusion from the tubotympanum in allergicinduced OME in guinea pigs.…”
Section: Discussionsupporting
confidence: 93%
“…Albumin concentration in the middle ear exudates was also reduced with the addition of OLO. Our work supports the results of Suzuki et al 23 that demonstrated that oral AZE promoted the evacuation of middle ear effusion from the tubotympanum in allergicinduced OME in guinea pigs.…”
Section: Discussionsupporting
confidence: 93%
“…Beneficial effects of anti‐allergic medicine against OME complicated with AR were confirmed by experimental studies using animal models [36]. After oral treatment with AZ, the number of animals having MEE was significantly reduced in a dose‐dependent manner in the group of animals with OME and AR but not in those without AR, suggesting that AZ promotes the evacuation of MEE from the tubotympanum in this OME animal model associated with AR.…”
Section: Ar and Function Of The Eustachian Tubementioning
confidence: 66%
“… 55 In addition, many studies have shown that the use of intra-aural antihistamines in sensitized rat models can reduce the accumulation of middle ear fluid, improve OME symptoms, and may be effective in treating ETD caused by allergies. 56 , 57 , 58 …”
Section: Application Of Anti-allergic Therapy In the Development Of Etdmentioning
confidence: 99%